2021
DOI: 10.1016/j.jemermed.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Personal Protective Equipment Masks on Health Care Workers’ Cardiopulmonary Resuscitation Performance During the Covid-19 Pandemic

Abstract: Background Personal protective equipment (PPE) are equipment that protect healthcare workers from harmful agents and organisms. The importance of these equipment was noticed again with the Covid-19 pandemic. Objectives In this study, we investigated the effect of different masks used as PPE on resuscitation quality and rescuer fatigue. Methods Participants applied chest compression without a mask, with a surgical mask, a filtering face-piece … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Chen et al reported that PPE usage reduces the parameters of compression rate, compression depth, and fully released compression rate [4] . In another study, it has been reported that the quality of CPR decreases with improved mask quality [13] . Donoghue et al reported that there was no deterioration in CPR quality relevant to PPE usage in their study involving paediatric manikins [5] .…”
Section: Discussionmentioning
confidence: 91%
“…Chen et al reported that PPE usage reduces the parameters of compression rate, compression depth, and fully released compression rate [4] . In another study, it has been reported that the quality of CPR decreases with improved mask quality [13] . Donoghue et al reported that there was no deterioration in CPR quality relevant to PPE usage in their study involving paediatric manikins [5] .…”
Section: Discussionmentioning
confidence: 91%
“… Hospitals and the general public Cost-friendly, single time usage, fluid-resistant, lower adverse health risk, useful while CPR ( Li, Zhao et al, 2021 ) Filtering facepiece respirator(N95) Filter outs 5–50 μm aerosols. Majorly by health care workers Face sealing property, reduced microplastic inhalation risk, increased CO 2 retention and humidity, eye dryness problem, not fit for a longer duration ( Ahmad et al, 2020 ; Boccardo, 2021 ; Serin & Caglar, 2020 ) Half face mask (P3 filter) Filters 80% of aerosols. At the crowded, dusty place Does not slip from the face, durable for 8 hours, increased fatigue during CPR ( Leung et al, 2020 ; Serin & Caglar, 2020 ) Cloth mask Prevents particles of diameter >200 nm.…”
Section: Indoor Air Quality Improvementmentioning
confidence: 99%
“… Majorly by health care workers Face sealing property, reduced microplastic inhalation risk, increased CO 2 retention and humidity, eye dryness problem, not fit for a longer duration ( Ahmad et al, 2020 ; Boccardo, 2021 ; Serin & Caglar, 2020 ) Half face mask (P3 filter) Filters 80% of aerosols. At the crowded, dusty place Does not slip from the face, durable for 8 hours, increased fatigue during CPR ( Leung et al, 2020 ; Serin & Caglar, 2020 ) Cloth mask Prevents particles of diameter >200 nm. Indoor usage by the general public Affordable, reusable, loose-fitting, less effective against viruses, not fluid resistant ( Davies et al, 2013 ; Leung et al, 2020 ) …”
Section: Indoor Air Quality Improvementmentioning
confidence: 99%
See 2 more Smart Citations